Embracing political economy to enhance influence: Lessons from PIM research - Resnick, Danielle (International Food Policy Research Institute, 2021)
An overarching goal of the CGIAR Research Program on Policies, Institutions, and Markets (PIM) has been to influence outcomes in ways that lead to agricultural transformation and economic inclusion. The technical quality of this research is well recognized (CAS Secretariat 2020). Yet, high-quality, rigorous research is not sufficient to achieve influence in any domain. Other factors may shape uptake — for instance, elections may alter priorities, ideological biases may hinder the acceptance of research findings, and vested interest groups may lobby against data-driven or evidence-informed recommendations. A political economy perspective allows for a more holistic and realistic understanding of how policies are determined by governments and which pathways are more viable for achieving development outcomes through change.